Staying safe and saving precious lives: Pediatric life support during COVID-19 pandemic and beyond - Mohamad-Hani Temsah (Wolters Kluwer Medknow Publications, 2020)
As COVID-19 was declared a pandemic by the World Health Organization in March 2020, the global community became on the alert toward optimizing patients' outcomes while maintaining the safety of health-care workers (HCWs). Providing cardiopulmonary resuscitation (CPR) to COVID-19 victims is further challenging, especially in the pediatric age group. This review describes the changes in the pediatric CPR guidelines after COVID-19, as well as potential resources to improve the patients' outcomes while maintaining HCWs' safety. We conducted a literature review on PubMed for all peer-reviewed publications on CPR in children with confirmed or suspected COVID-19. The search on June 25, 2020, retrieved the following results: "pediatric life support" AND COVID-19 (30 papers); CPR AND children AND COVID-19 (6 papers) CPR devise AND COVID-19 (11 papers). Twenty-four papers were retrieved after accounting for duplications. All the reviewed CPR guidelines in suspected or confirmed COVID-19 pediatric patients emphasize balancing the immediate needs of the victims with the priority of HCWs' own safety. Furthermore, in the pediatric age group, the rapid initiation of respiratory support is key to improving the outcome. We, therefore, recommend early recognition of the rapidly deteriorating child, such as through the Pediatric Rapid Response Team (PRRT), since such proactive measures could avoid risky CPR. This proactive PRRT would be much needed in the coming winter season, when more children may require critical care services. Implications of key findings: Early recognition of the rapidly deteriorating child to avoid or quickly prepare for possible CPR is advisable. Planning for the pediatric code teams before the next winter season is warranted.